Appointment of new PGA UMPSA leadership empowers postgraduate students - Nur Ainaa Adhreena, Muhamad Shukri (UMPSA, 2025)
KUANTAN, 24 March 2025 – A total of 15 postgraduate students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) have been entrusted as the new leadership of the UMPSA Postgraduate Association (PGA) for the 2025 session during the UMPSA PGA Appointment Letter Handover Ceremony recently.